A breakthrough in the artificial cultivation of Chinese cordyceps on a large-scale and its impact on science, the economy, and industry. (17th February 2019) - Li, Xiao; Liu, Qing; Li, Wenjia; Li, Quanping; Qian, Zhengming; Liu, Xingzhong; Dong, Caihong
Abstract: Chinese cordyceps, an entity of the Chinese caterpillar fungus ( Ophiocordyceps sinensis, syn. Cordyceps sinensis ) that parasitizes ghost moth larvae, is one of the best known traditional Chinese medicines and is found exclusively on the Tibetan Plateau with limited natural resources. Although the fungus O. sinensis can grow on artificial substrates and the ghost moth has been successfully reared, the large-scale artificial cultivation of Chinese cordyceps has only recently been accomplished after several decades of efforts and attempts. In this article, research progress related to this breakthrough from living habitats, the life history of the fungus, its host insect, fungal isolation and culture, host larvae rearing, infection cycle of the fungus to the host, primordium induction, and fruiting body development have been reviewed. An understanding of the basic biology of O. sinensis, its host insect and the simulation of the Tibetan alpine environment resulted in the success of artificial cultivation on a large scale. Practical workshop production has reached annual yields of 2.5, 5, and 10 tons in 2014, 2015, and 2016, respectively. There was no difference in the chemical components detected between the cultivated and natural Chinese cordyceps. However, the artificial cultivation system can be controlled to avoid heavy metal contamination and results in high-quality products. Although omics studies, including genomic, transcriptomic, proteomic, and metabolomic studies, have helped to understand the biology of the fungus, the success of the artificial cultivation of the Chinese cordyceps is clearly a milestone and provides the possibility for research on the in-depth mechanisms of the interaction between the fungus and host insects and their adaptation to the harsh habitats. This cultivation will not only result in a large industry to alleviate the pressure of human demand but also protect the limited natural resources for sustainable utilization.